Implementasi Aplikasi Database Untuk Mendukung Sistem Smart card Di STKIP Muhammadiyah Bone - Andani Achmad; Rhiza S. Sadjad; Muh Anshar; Zaenab Muslimin; Indrabayu Indrabayu; Syafruddin Syarif; Zulfajri B. Hasanuddin; Andini D. Achmad (Faculty of Engineering UNHAS, 2019)
Smart campus refers to campus facilities which are supporting all activities of the academics in carrying out the obligations of the Tridarma Perguruan Tinggi using information technology as the backbone. STKIP Muhammadiyah Bone was chosen as a partner in the community service program. In order to welcome a transformation, the campus will direct its services with technology. Currently services such as student registration, attendance input is still done mannually, in the future it will be converted into an electronic system. However, in STKIP Muhammadiyah Bone, it has not applied smart campus system. The proposed solution is to make Smart cards socialization and training and database implementation. After thorough socialization and training which includes hardware, software, procedures and work procedures, furthermore, independent development is carried out by the campus itself. This activity was held for one day and went smoothly judging from the enthusiasm of the staff and students who participated in this activity and the installation of two smartcard systems in the rector and vice rector rooms.